El silencio en la educación: Análisis bibliográfico - Rodríguez Chávez, Franky Steven (Universidad Antonio Nariño, 2021)
The following work is a compilation monograph that aims to work silence in the educational field, likewise seeks to encourage the reflection of the different perspectives of silence, its definition, its access routes along with its implementation